Predicted Effects and Cost-Effectiveness of Wheat Flour Fortification for Reducing Micronutrient Deficiencies, Maternal Anemia, and Neural Tube Defects in Yaoundé and Douala, Cameroon. Issue 4 (December 2021) - Noshirvan, Arram; Wu, Brenda; Luo, Hanqi; Kagin, Justin; Vosti, Stephen A.; Ndjebayi, Alex; Assiene, Jules Guintang; Teta, Ismael; Nankap, Martin; Engle-Stone, Reina
Background: Policy makers aiming to reduce micronutrient deficiencies (MNDs) and their health effects must choose among alternative definitions of impact when evaluating cost-effectiveness. Objective: Estimate the cost-effectiveness of a mandatory wheat flour fortification program for reducing cases of MNDs (iron, zinc, folate, vitamin B12), anemia and neural tube defects (NTDs) averted, and disability-adjusted life years (DALYs) averted in urban Cameroon. Methods: A 13-year predictive model was developed, including a 3-year start-up period and 10 years of program activity. Costs were estimated using historical program budgets. Effects were calculated based on observed changes in prevalence of MND and anemia 1 year postfortification and predicted reductions in NTDs based on NTD burden and wheat flour intake. Total DALYs averted were estimated for anemia and NTDs. Results: The program cost ∼2.4 million over 13 years and averted an estimated ∼95 000 cases of maternal anemia and ∼83 500 cases of iron deficiency among children after 1 year. Cost/case-year averted for MNDs ranged from 0.50 for low plasma folate to 3.30 for iron deficiency and was 2.20 for maternal anemia. The program was predicted to avert 1600 cases of NTDs over 10 years at ∼1500 per case averted. Estimated cost/DALY averted was 50 for NTDs and 115 for anemia. Conclusions: In Cameroon, cost-effectiveness of wheat flour fortification varied by the measure of impact employed, but was classified as "very cost-effective" for all outcomes using World Health Organization criteria. Policy makers and their advisors must determine how best to use information on program costs and benefits to inform their decisions.